Kebijakan Pendidikan pada Masa Kabinet Ali Sastroamidjojo I Pascakemerdekaan, 1953-1955 - Offy Resdiantari; Zulkarnain Zulkarnain (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2025)
This research aims to discuss education policies during the Ali Sastroamidjojo I Cabinet (1953-1955), including their impact on the Indonesian nation after independence. The research method used is the historical research method which includes the stages of heuristics, criticism, interpretation, and historiography. The approach used in this paper uses the decolonization paradigm in the field of knowledge. The periodization in this study is limited from 1953 to 1955 in order to analyze more deeply the education policies implemented during the Ali Sastroamidjojo I Cabinet. The results of this study found that education policies during the Ali Sastroamidjojo I Cabinet succeeded in realizing Law Number 4 of 1950. This is represented by Yamin's actions as Minister of PP and K who continued and developed the Rentjana Peladjaran Terurai (1952) as the education curriculum during the Ali Cabinet. Yamin also supports additional assistance from the government for elementary, secondary, and vocational schools, including private schools. In addition, the opening of universities in 1954 that covered various disciplines also had an impact on Indonesia's educational climate, which became better than before.